Silencing-associated and meiosis-specific small RNA pathways in Paramecium tetraurelia - Lepère, Gersende (Oxford University Press, 2009)
Distinct small RNA pathways are involved in the two types of homology-dependent effects described in Paramecium tetraurelia, as shown by a functional analysis of Dicer and Dicer-like genes and by the sequencing of small RNAs. The siRNAs that mediate post-transcriptional gene silencing when cells are fed with double-stranded RNA (dsRNA) were found to comprise two subclasses. DCR1-dependent cleavage of the inducing dsRNA generates ∼23-nt primary siRNAs from both strands, while a different subclass of ∼24-nt RNAs, characterized by a short untemplated poly-A tail, is strictly antisense to the targeted mRNA, suggestive of secondary siRNAs that depend on an RNA-dependent RNA polymerase. An entirely distinct pathway is responsible for homology-dependent regulation of developmental genome rearrangements after sexual reproduction. During early meiosis, the DCL2 and DCL3 genes are required for the production of a highly complex population of ∼25-nt scnRNAs from all types of germline sequences, including both strands of exons, introns, intergenic regions, transposons and Internal Eliminated Sequences. A prominent 5′-UNG signature, and a minor fraction showing the complementary signature at positions 21–23, indicate that scnRNAs are cleaved from dsRNA precursors as duplexes with 2-nt 3′ overhangs at both ends, followed by preferential stabilization of the 5′-UNG strand.